Approaching a "Naked" Boryl Anion: Amide Metathesis as a Route to Calcium, Strontium, and Potassium Boryl Complexes. Issue 4 (23rd November 2020) - Protchenko, Andrey V.; Vasko, Petra; Fuentes, M. Ángeles; Hicks, Jamie; Vidovic, Dragoslav; Aldridge, Simon
Abstract: Amide metathesis has been used to generate the first structurally characterized boryl complexes of calcium and strontium, {(Me3 Si)2 N}M{B(NDippCH)2 }(thf) n (M=Ca, n =2; M=Sr, n =3), through the reactions of the corresponding bis(amides), M{N(SiMe3 )2 }2 (thf)2, with (thf)2 Li‐ {B(NDippCH)2 }. Most notably, this approach can also be applied to the analogous potassium amide K{N(SiMe3 )2 }, leading to the formation of the solvent‐free borylpotassium dimer [K{B(NDippCH)2 }]2, which is stable in the solid state at room temperature for extended periods (48 h). A dimeric structure has been determined crystallographically in which the K + cations interact weakly with both the ipso‐carbons of the flanking Dipp groups and the boron centres of the diazaborolyl heterocycles, with K⋅⋅⋅B distances of >3.1 Å. These structural features, together with atoms in molecules (QTAIM) calculations imply that the boron‐containing fragment closely approaches a limiting description as a "free" boryl anion in the condensed phase. Abstract : Amide metathesis is exploited as a route to boryl compounds of K, Ca, and Sr. The dimeric potassium system is shown by crystallographic and atoms‐in‐molecules studies to approach a limiting description as a "free" boryl anion.